Anchorage of bacterial effector at plasma membrane via selective phosphatidic acid binding to modulate host cell signaling. - Meng Wang; Qixiao Guan; Chunyan Wang; Lyubin Hu; Xueyan Hu; Menglin Xu; Yuhao Cai; Haoran Zhang; Qing Cao; Huiming Sheng; Xiaohui Wei; Jane E Koehler; et al. (PLoS Pathogens)
Binding phospholipid is a simple, yet flexible, strategy for anchorage of bacterial effectors at cell membrane to manipulate host signaling responses. Phosphatidylinositol 4-phosphate and phosphatidylinositol 4,5-biphosphate are the only two phospholipid species known to direct bacterial effectors to establish inner leaflet localization at the plasma membrane. Here, selectivity of phosphatidic acid (PA) by bacterial effectors for the plasma membrane anchorage and its molecular entity was identified. C-terminal BID domain of Bartonella T4SS effectors (Beps) directed the plasma membrane localization of Beps in host cells through binding with PA. A hydrophobic segment of the 'HOOK' subdomain from BID is inserted into the bilayer to enhance the interaction of positively charged residues with the lipid headgroups. Mutations of a conserved arginine facilitating the electrostatic interaction, a conserved glycine maintaining the stability of the PA binding groove, and hydrophobic residues determining membrane insertion, prevented the anchorage of Beps at the plasma membrane. Disassociation from plasma membrane to cytosol attenuated the BepC capacity to induce stress fiber formation and cell fragmentation in host cells. The substitution of alanine with aspartic acid at the -1 position preceding the conserved arginine residue hindered BepD anchoring at the plasma membrane, a vital prerequisite for its ability to elicit IL-10 secretion in host macrophages. In conclusion, our findings reveal the PA-binding properties of bacterial effectors to establish plasma membrane localization and will shed light on the intricate mechanisms employed by bacterial effectors within host cells.